2022
DOI: 10.1177/23259671211068079
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of NCAA Track and Field Injuries From 2010 to 2014

Abstract: Background: Track and field (T&F) athletes compete in a variety of events that require different skills and training characteristics. Descriptive epidemiology studies often fail to describe event-specific injury patterns. Purpose: To describe the epidemiology of injuries in National Collegiate Athletic Association (NCAA) T&F by sex, setting (practice vs competition), and time of season (indoor vs outdoor) and to compare injury patterns by events within the sport. Study Design: Descriptive epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Overall, females (8,294; 95% CI: 7,087-9,502) Despite the popularity of track and field, limited research has investigated this population at large. Many studies have instead focused on National Collegiate Athletic Association (NCAA) or elite level athletes specifically [3][4][5][6]. Even less research has focused on throwing event injury patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, females (8,294; 95% CI: 7,087-9,502) Despite the popularity of track and field, limited research has investigated this population at large. Many studies have instead focused on National Collegiate Athletic Association (NCAA) or elite level athletes specifically [3][4][5][6]. Even less research has focused on throwing event injury patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, hurdle races are divided based upon age and sex, so an understanding of how injuries differ between the different groups is warranted [ 3 ]. On the collegiate level, there has been an analysis of sex differences in track and field injuries [ 9 ], but hurdling was not included in the study. Sex-specific studies of all track and field injuries, which included those sustained in hurdling, have been performed and have evaluated injured body parts and mechanisms [ 10 , 11 ], but, similarly, these have been limited to collegiate athletes and have not compared injuries across the two sexes.…”
Section: Introductionmentioning
confidence: 99%
“…During elite athletics championships, the most prevalent injury diagnosis has been thigh strains (especially hamstring strain with 16%), and 46% of them have led to time loss from training [2,3]. Hopkins et al found that, in the seasons 2010-2014, track and field athletes of the National Collegiate Athletic Association had injury prevalence of 3.99 injuries per 1000 athletic exposures [20].…”
Section: Introductionmentioning
confidence: 99%